3D printed versus conventionally cured provisional crown and bridge dental materials. Issue 2 (February 2018) - Tahayeri, Anthony; Morgan, MaryCatherine; Fugolin, Ana P.; Bompolaki, Despoina; Athirasala, Avathamsa; Pfeifer, Carmem S.; Ferracane, Jack L.; Bertassoni, Luiz E.
Highlights: Provisional crown and bridge resins were 3D printed using a low-cost stereolithography 3D printer. The elastic modulus and peak stress of 3D printed samples was comparable or higher than that of Jet ® . Temporary crowns can be 3D printed with adequate mechanical properties for intraoral use. Abstract: Objectives: To optimize the 3D printing of a dental material for provisional crown and bridge restorations using a low-cost stereolithography 3D printer; and compare its mechanical properties against conventionally cured provisional dental materials. Methods: Samples were 3D printed (25 × 2 × 2 mm) using a commercial printable resin (NextDent C&B Vertex Dental) in a FormLabs1+ stereolithography 3D printer. The printing accuracy of printed bars was determined by comparing the width, length and thickness of samples for different printer settings (printing orientation and resin color) versus the set dimensions of CAD designs. The degree of conversion of the resin was measured with FTIR, and both the elastic modulus and peak stress of 3D printed bars was determined using a 3-point being test for different printing layer thicknesses. The results were compared to those for two conventionally cured provisional materials (Integrity ®, Dentsply; and Jet ®, Lang Dental Inc.). Results: Samples printed at 90° orientation and in a white resin color setting was chosen as the most optimal combination of printing parameters, due to the comparatively higher printing accuracy (up to 22% error), reproducibility and material usage. There was no direct correlation between printing layer thickness and elastic modulus or peak stress. 3D printed samples had comparable modulus to Jet ®, but significantly lower than Integrity ® . Peak stress for 3D printed samples was comparable to Integrity ®, and significantly higher than Jet ® . The degree of conversion of 3D printed samples also appeared higher than that of Integrity ® or Jet ® . Significance: Our results suggest that a 3D printable provisional restorative material allows for sufficient mechanical properties for intraoral use, despite the limited 3D printing accuracy of the printing system of choice.